1998
DOI: 10.1177/074873098128999989
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Hypothesis of a Circadian Phase Disturbance Underlying Depressive Mood in Nonseasonal Depression

Abstract: In a crossover design, 8 nonseasonal depressed subjects, selected on the presence of diurnal mood variations, and 8 sex and age-matched controls were exposed to dim light (< 10 lux) in the evening (18:00-21:00 h) and bright light (2500 lux) in the morning (ML, 6:00-9:00 h), to dim light in the morning and bright light in the evening (EL), or to dim light both in the evening and in the morning (DL) during 3 consecutive days in each of these conditions. There were no initial phase differences between depresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…A study of 17 SAD patients and controls reported that light-associated temperaure decreases are in direct proportion to antidepressant responses (Schwartz et al 1997b). A review of the literature in major depression suggests that bright light therapy is not as effective for treatment of nonseasonal depression as compared with seasonal depression (Gordijn et al 1998;Thalaen et al 1997). However, some nonseasonal patients may show improvement (Dietzel et al 1986;Kripke, 1998;Yamada et al 1995).…”
Section: Bright Light Therapymentioning
confidence: 99%
“…A study of 17 SAD patients and controls reported that light-associated temperaure decreases are in direct proportion to antidepressant responses (Schwartz et al 1997b). A review of the literature in major depression suggests that bright light therapy is not as effective for treatment of nonseasonal depression as compared with seasonal depression (Gordijn et al 1998;Thalaen et al 1997). However, some nonseasonal patients may show improvement (Dietzel et al 1986;Kripke, 1998;Yamada et al 1995).…”
Section: Bright Light Therapymentioning
confidence: 99%
“…Most [16][17][18][19][20][21][22][23], but not all [24,25], of these studies showed disturbed circadian temperature rhythms in patients with depression and other mood disorders [26,27]. Some [22,[28][29][30], but not all [31], studies on depressed patients have documented high nocturnal temperatures and higher mean 24-hour temperatures [28].…”
Section: Introductionmentioning
confidence: 99%
“…Yerevanian et al 1986;Deltito et al 1991;Thalen et al 1995). No evidence was provided for the relationship between antidepressant and phaseshifting effects of bright light in non-SAD (Rao et al 1992;Yamada et al 1995;Gordijn et al 1998).…”
Section: Introductionmentioning
confidence: 75%
“…There were reports of both positive (Kripke et al 1983(Kripke et al , 1992Yamada et al 1995) and negative findings (Stinson & Thompson 1990;Mackert et al 1991;Gordijn et al 1998), as well as the reports indicating that the clinical response in non-seasonally depressed patients is modest compared to that in patients with winter depression (i.e. Yerevanian et al 1986;Deltito et al 1991;Thalen et al 1995).…”
Section: Introductionmentioning
confidence: 94%